Extended TAM and TTF model: A Framework for the 21st Century Teaching and Learning - Lim, T. L.; Lee, Angela Siew Hoong * (2021)
The use of Information and Communication Technology (ICT) in everyday life of an individual has expanded in recent years. The much-needed skills for 21 st century are creativity, able to think critically, communication and collaboration skills. By equipping students with these skills, it will able to prepare students for the challenges in life and work environments in 21 st century. The advancement of technology has led to e-learning in education. E-learning refers to online learning, which provides students with a virtual environment in which students engage in several activities. However, even with the increasingly utilise of e-learning platform, research has proven that the issues of students were not fully utilise the functions of e-learning platforms in their learning process still exist. It is just act as a supporting tool for them and lack of communication support provided by learning management system (LMS) has leads to using other platform for communication purposes. Pervasive tools in education such as mobile devices, wearable technology, and RFID has proven to have positive impact on student learning outcome, however its application in higher education settings is still relatively little. Hence with the limitations of current teaching practice with limitations of study focusing on utilizing pervasive tools, therefore the aim of this study is to investigate the important factors which affect the user behaviour of IT devices (pervasive tools). To achieve this, theories of technology acceptance model (TAM) and task technology fit (TTF) was used. Along with TAM and TTF characteristics, factors of enjoyment, usefulness, convenience, compatibility, social influence, computer self-efficacy, and mobility were also considered. This study provides a framework to better understand the factors affect the acceptance of pervasive tools in private universities in Malaysia.